Preparation method of high-temperature-resistant anti-corrosion aluminizing coating and prepared coating

By introducing modified sheet aluminum powder and metal oxides into the aluminized coating and forming a shielding layer, the problems of rough surface and internal cracks when the traditional aluminized coating are prepared in an air atmosphere are solved, and high efficiency and economicality are achieved The high-temperature anti-corrosion aluminized coating preparation improves the performance and process convenience of the coating.

CN119411064AActive Publication Date: 2025-02-11AVIC BEIJING INST OF AERONAUTICAL MATERIALS
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411367995.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-02-11
Estimated Expiration
2044-09-29

AI Technical Summary

Technical Problem

When traditional aluminized coating is prepared in an air atmosphere, the thickness of the alumina layer on the coating surface is uncontrollable, the surface roughness is high, and there are many cracks inside the coating, which affects the aerodynamic performance of the equipment, reduces the coating performance, and limits the promotion of the process. application.

Method used

Using a high-temperature anti-corrosion aluminized coating composed of an aluminized layer and a shielding layer, a modified sheet aluminum powder and metal oxide are introduced into the aluminized paste, and a shielding layer is formed on the surface of the coating, and the shielding layer is formed from The film resin, modified sheet filler and zirconium boride powder are composed of the aluminum diffusion process through heat treatment.

Benefits of technology

It realizes the preparation of high-temperature anti-corrosion aluminized coating under an air atmosphere, which reduces process costs and difficulty, improves the oxidation and corrosion resistance of the coating, reduces internal cracks of the coating, and enhances the aerodynamic performance of the equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119411064A_ABST
    Figure CN119411064A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a high-temperature-resistant anti-corrosion aluminizing coating and the prepared coating, and relates to the technical field of coating preparation. The method comprises the following steps: S1, preparing a percolation layer; S2, preparing a shielding layer; and S3, carrying out heat treatment on the coating in an air atmosphere. The high-temperature-resistant corrosion-resistant aluminizing coating is prepared in an air atmosphere, has excellent oxidation resistance and corrosion resistance, can tolerate thermal oxidation at 1000 DEG C for 100 hours and neutral salt spray corrosion for 3000 hours, and does not blister, crack or fall off.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of coating preparation, and in particular relates to a method for preparing a high-temperature resistant and anti-corrosion aluminized coating and the prepared coating. Background Art

[0002] Gas turbines and aircraft engines are the core power units of ships and aircraft. During their service in the marine environment, they must withstand long-term high-temperature oxidation and a complex corrosion environment coupled with salt spray corrosion, molten salt corrosion and gas thermal corrosion. In order to ensure the long-term and reliable service of the equipment, high-pressure compressor blades, casings and other adjacent parts with operating temperatures between 500℃ and 1000℃ are usually coated with aluminized coatings to achieve high-temperature corrosion protection. Traditional aluminized coatings are prepared by powder embedding, hot-dip aluminizing, slurry aluminizing and chemical vapor deposition. Although the process equipment and process procedures used in each method are significantly different, the core aluminum diffusion process needs to be carried out under the protection of an inert atmosphere such as vacuum or high-purity argon, which greatly increases the cost and difficulty of the aluminized coating preparation process. The reactive aluminizing process in air atmosphere, which is further developed based on the slurry aluminizing process, has inherited the characteristics of short heat treatment cycle, high utilization rate of aluminizing raw materials and high applicability of complex structures, and has made attempts to reduce the cost and facilitate the process. However, the thickness of the aluminum oxide layer on the coating surface is uncontrollable, the high surface roughness affects the aerodynamic performance of the equipment, and there are many cracks inside the coating, which greatly reduces the coating performance and limits the promotion and application of this process. Therefore, it is necessary to develop a material and process that can block oxygen for the aluminum diffusion process in air atmosphere. In response to this, this patent proposes a high-temperature resistant and anti-corrosion aluminizing coating composed of an aluminizing layer and a shielding layer and a preparation method thereof in air atmosphere. Summary of the invention

[0003] Based on the above background, the present invention aims to provide a high-temperature resistant anti-corrosion aluminizing coating and a preparation method thereof in an air atmosphere for high-pressure compressor blades, casings and other adjacent components in gas turbines and aircraft engines with operating temperatures between 500°C and 1000°C.

[0004] In view of this, according to one aspect of an embodiment of the present invention, a method for preparing a high temperature resistant and anti-corrosion aluminized coating is provided, comprising:

[0005] Step S1: Preparation of the infiltration layer: The aluminized slurry is applied on the metal substrate by air spraying, dipping or brushing. After the coating is completely dried, the aluminized slurry layer is obtained. The film thickness of the aluminized slurry layer after drying is controlled to be 30 to 50 μm. The metal substrate coated with the aluminized slurry layer is directly placed in 450 to 500° C. for 5 to 10 minutes of thermal debonding, and then cooled to room temperature in an air atmosphere to obtain the aluminized layer.

[0006] Step S2: Preparation of shielding layer: Apply shielding coating on the surface of aluminized layer by air spraying or brushing, and obtain shielding layer after the coating is completely dry, and control the total film thickness of shielding layer and aluminized layer to be no more than 80 μm;

[0007] Step S3: Heat treatment of the coating in air atmosphere: heat the metal substrate coated with the aluminized layer and the shielding layer to 500°C at a heating rate of 1-2°C / min, keep it warm for 30-60 minutes, then heat it to 700°C at a heating rate of 5-10°C / min, keep it warm for 1.5-2 hours, cool it to 150°C at a cooling rate of 10-15°C / min, and then cool it to room temperature in air. The metal substrate is then coated with the high temperature resistant and anti-corrosion aluminized coating.

[0008] Optionally, step S1 also includes the preparation of modified flaky aluminum powder:

[0009] Take a solvent such as toluene, xylene or n-hexane to dissolve terminal methyl or terminal vinyl polysilazane, the mass ratio of polysilazane to solvent is 1:15-25, recorded as solution A, take the same solvent to dissolve terminal hydroxyl polydimethylsiloxane, the mass ratio of terminal hydroxyl polydimethylsiloxane to solvent is 1:5-10, recorded as solution B, disperse flaky aluminum powder in solution A, the mass ratio of the two is 1:5-10, after the dispersion temperature is stable, weigh solution B and add it dropwise into solution A, the mass ratio of solution A to solution B is 1:0.3-0.5, after the dropwise addition is completed, under nitrogen atmosphere and condensation reflux, stir the reaction in an oil bath at 120-150°C for 2-3h, filter the product and wash it with acetone for multiple times, place it in a vacuum at 50-80°C and dry it for 6-8h to obtain modified flaky aluminum powder.

[0010] Optionally, step S1 also includes the preparation of aluminizing slurry: weighing a binder, an associative polyurethane thickener, spherical aluminum powder, modified flaky aluminum powder, a metal oxide and a solvent according to a mass ratio, first dissolving the binder in the solvent, and after the solvent is clarified, dispersing the binder solution, the associative polyurethane thickener, the spherical aluminum powder, the modified flaky aluminum powder and the metal oxide at a high speed in a constant temperature water area of ​​10 to 25°C to finally obtain aluminizing slurry.

[0011] Optionally, step S2 also includes the preparation of a modified anti-corrosion filler: dispersing hexagonal boron nitride in a 70% to 95% ethanol-water solution, adjusting the dispersion to a weakly acidic state using formic acid or acetic acid; adding one of trimethylmethoxysilane and vinyltriethoxysilane in a mass ratio of 0.01 to 0.05:1 to hexagonal boron nitride to the mixture, stirring the reaction in a water bath at 40 to 80°C with condensation reflux for 1 to 3 hours, filtering and washing the product, and drying it at 80 to 90°C to obtain a modified anti-corrosion filler.

[0012] Optionally, the method further comprises the preparation of a shielding coating: the modified film-forming resin, the modified anticorrosive filler, various additives and the diluent are weighed according to the mass ratio, mixed and ground, and the particle size of the mixture is less than 25 μm, to obtain a shielding coating.

[0013] Optionally, the spherical aluminum powder accounts for 35-50% of the mass of the aluminizing slurry.

[0014] Optionally, the modified flaky aluminum powder accounts for 3-6% of the mass of the aluminizing slurry, and is a flaky aluminum powder coated with a copolymer of terminal hydroxyl polydimethylsiloxane and polysilazane.

[0015] Optionally, the metal oxide accounts for 0.5-1% of the mass of the aluminizing slurry and is one of cerium oxide and zirconium oxide.

[0016] Optionally, the spherical aluminum powder is composed of a compound of spherical aluminum powders with particle size distribution concentrated in 5-10 μm and 25-40 μm, and the mass ratio of the two is 6-8:2-4.

[0017] According to another aspect of an embodiment of the present invention, a high temperature resistant and anti-corrosion aluminized coating is provided, which is prepared by any of the above methods, wherein the coating comprises an aluminized layer and a shielding layer, wherein the aluminized layer is formed by drying and thermally removing the aluminized slurry, and the shielding layer is formed by heating and curing the shielding coating, and the coating is finally formed by completing the aluminum diffusion process through heat treatment.

[0018] Advantages of the present invention include:

[0019] 1. The coating is composed of an aluminized layer and a shielding layer. The cross-linked and cured shielding layer blocks oxygen in the air during the aluminum diffusion process, so that the process no longer needs to be carried out under the protection of an inert atmosphere such as vacuum or high-purity argon, greatly reducing the cost and difficulty of the aluminized coating preparation process.

[0020] 2. The modified flaky aluminum powder in the aluminizing layer provides silicon elements to the aluminum diffusion process on the one hand, regulating the diffusion activity; on the other hand, it adjusts the internal stress of the coating during the heat treatment process, making it less likely to produce cracks inside the aluminizing coating.

[0021] 3. Zirconium boride is introduced into the shielding layer. At high temperature, zirconium boride is oxidized to form zirconium oxide and boron oxide. The boron oxide melts and forms a molten film layer on the outer surface of the shielding layer through capillary action, further blocking oxygen.

[0022] The performance advantages of the high temperature resistant and anti-corrosion aluminized coating are:

[0023] Excellent high temperature resistance and anti-corrosion performance: It can provide nearly 1000 hours of long-term high temperature corrosion protection for iron-based and nickel-based high temperature alloys with an operating temperature range of 500-1000°C; between 500-700°C, the shielding layer can block the corrosive medium and oxygen, and almost no corrosion or oxidation consumption is caused to the aluminized coating, thus improving the corrosion resistance of the coating;

[0024] Convenient process: short heat treatment cycle, high utilization rate of aluminizing raw materials and high applicability of complex structures. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The present invention is a flow chart of a method for preparing a high temperature resistant and anti-corrosion aluminizing coating. DETAILED DESCRIPTION

[0026] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] According to one aspect of an embodiment of the present invention, a method for preparing a high temperature resistant and anti-corrosion aluminized coating is provided, comprising:

[0028] Step S1: Preparation of the infiltration layer: The aluminized slurry is applied on the metal substrate by air spraying, dipping or brushing. After the coating is completely dried, the aluminized slurry layer is obtained. The film thickness of the aluminized slurry layer after drying is controlled to be 30 to 50 μm. The metal substrate coated with the aluminized slurry layer is directly placed in 450 to 500° C. for 5 to 10 minutes of thermal debonding, and then cooled to room temperature in an air atmosphere to obtain the aluminized layer.

[0029] Step S2: Preparation of shielding layer: Apply shielding coating on the surface of aluminized layer by air spraying or brushing, and obtain shielding layer after the coating is completely dry, and control the total film thickness of shielding layer and aluminized layer to be no more than 80 μm;

[0030] Step S3: Heat treatment of the coating in air atmosphere: heat the metal substrate coated with the aluminized layer and the shielding layer to 500°C at a heating rate of 1-2°C / min, keep it warm for 30-60 minutes, then heat it to 700°C at a heating rate of 5-10°C / min, keep it warm for 1.5-2 hours, cool it to 150°C at a cooling rate of 10-15°C / min, and then cool it to room temperature in air. The metal substrate is then coated with the high temperature resistant and anti-corrosion aluminized coating.

[0031] Furthermore, step S1 also includes the preparation of modified flaky aluminum powder:

[0032] Take a solvent such as toluene, xylene or n-hexane to dissolve terminal methyl or terminal vinyl polysilazane, the mass ratio of polysilazane to solvent is 1:15-25, recorded as solution A, take the same solvent to dissolve terminal hydroxyl polydimethylsiloxane, the mass ratio of terminal hydroxyl polydimethylsiloxane to solvent is 1:5-10, recorded as solution B, disperse flaky aluminum powder in solution A, the mass ratio of the two is 1:5-10, after the dispersion temperature is stable, weigh solution B and add it dropwise into solution A, the mass ratio of solution A to solution B is 1:0.3-0.5, after the dropwise addition is completed, under nitrogen atmosphere and condensation reflux, stir the reaction in an oil bath at 120-150°C for 2-3h, filter the product and wash it with acetone for multiple times, place it in a vacuum at 50-80°C and dry it for 6-8h to obtain modified flaky aluminum powder.

[0033] Furthermore, step S1 also includes the preparation of aluminizing slurry: weighing a binder, an associative polyurethane thickener, spherical aluminum powder, modified flaky aluminum powder, a metal oxide and a solvent according to a mass ratio, first dissolving the binder in the solvent, and after the solvent is clarified, dispersing the binder solution, the associative polyurethane thickener, the spherical aluminum powder, the modified flaky aluminum powder and the metal oxide at a high speed in a constant temperature water area of ​​10 to 25°C to finally obtain aluminizing slurry.

[0034] Furthermore, step S2 also includes the preparation of a modified anti-corrosion filler: dispersing hexagonal boron nitride in a 70% to 95% ethanol-water solution, adjusting the above dispersion to a weakly acidic state using formic acid or acetic acid for standby use; adding one of trimethylmethoxysilane and vinyltriethoxysilane in a mass ratio of 0.01 to 0.05:1 to hexagonal boron nitride to the mixture, stirring the reaction in a water bath at 40 to 80°C with condensation reflux for 1 to 3 hours, filtering and washing the product, and drying it at 80 to 90°C to obtain a modified anti-corrosion filler.

[0035] Furthermore, the method also includes the preparation of shielding coating: modified film-forming resin, modified anticorrosive filler, various additives and diluents are weighed according to the mass ratio, mixed and ground, and the particle size of the mixture is less than 25 μm to obtain shielding coating.

[0036] Furthermore, the spherical aluminum powder accounts for 35-50% of the mass of the aluminizing slurry.

[0037] Furthermore, the modified flaky aluminum powder accounts for 3-6% of the mass of the aluminizing slurry, and is a flaky aluminum powder coated with a copolymer of terminal hydroxyl polydimethylsiloxane and polysilazane.

[0038] Furthermore, the metal oxide accounts for 0.5-1% of the mass of the aluminizing slurry and is one of cerium oxide and zirconium oxide.

[0039] Furthermore, the spherical aluminum powder is composed of a compound of spherical aluminum powders with particle size distribution concentrated in 5-10 μm and 25-40 μm, and the mass ratio of the two is 6-8:2-4.

[0040] Furthermore, the binder accounts for 3-5% of the mass of the aluminizing slurry, and is mainly one of polyethylene glycol and polyvinyl alcohol.

[0041] Furthermore, the associative polyurethane thickener accounts for 0.5-2% of the mass of the aluminizing slurry.

[0042] Furthermore, the modified flaky aluminum powder accounts for 3-6% of the mass of the aluminizing slurry, and is mainly flaky aluminum powder coated with a copolymer of terminal hydroxyl polydimethylsiloxane and polysilazane.

[0043] Furthermore, the metal oxide accounts for 0.5-1% of the mass of the aluminizing slurry, and is mainly one of cerium oxide and zirconium oxide.

[0044] Furthermore, the balance of the aluminizing slurry mass is solvent, mainly deionized water.

[0045] Furthermore, the number average molecular weight of polyethylene glycol and polyvinyl alcohol should be controlled between 10,000 and 30,000;

[0046] Furthermore, the associative polyurethane thickener is mainly composed of a non-ionic polyether polyurethane having a number average molecular weight controlled between 3500 and 6000;

[0047] Further, the associative polyurethane thickener is preferably the commercially available product BYK RHEOBYK-H7625VF and One of the Viscoplus 3030;

[0048] Furthermore, the flake diameter distribution of the flaky aluminum powder is concentrated between 15 and 25 μm.

[0049] Furthermore, the number average molecular weight of the hydroxy-terminated polydimethylsiloxane used for coating and modifying the flaky aluminum powder should be controlled between 2500 and 3000.

[0050] Furthermore, the number average molecular weight of the polysilazane used for coating and modifying the flaky aluminum powder should be controlled between 1000 and 1500, and the active group is methyl or vinyl.

[0051] Furthermore, the particle size distribution of the metal oxide is concentrated between 5 and 10 μm.

[0052] Furthermore, the film-forming resin accounts for 40-50% of the mass of the shielding coating, and is mainly methyl-terminated or vinyl-terminated perhydropolysilazane.

[0053] Furthermore, the modified flake filler accounts for 10-15% of the mass of the shielding coating, and is mainly silane-modified hexagonal boron nitride.

[0054] Furthermore, zirconium diboride powder accounts for 5-8% of the mass of the shielding coating.

[0055] Furthermore, the functional additive accounts for 1% to 2% of the mass of the shielding coating, and is mainly composed of a dispersant and an anti-precipitation additive.

[0056] Further, the remainder of the shielding coating mass is a diluent, which is mainly composed of xylene and butyl acetate.

[0057] Furthermore, the number average molecular weight of the methyl-terminated or vinyl-terminated perhydropolysilazane should be controlled to be between 1000 and 1500.

[0058] Furthermore, the hexagonal boron nitride used for modifying the flake filler has a flake diameter distribution concentrated between 15 and 25 μm.

[0059] Furthermore, the silane used for modifying the hexagonal boron nitride is preferably one of trimethylmethoxysilane and vinyltriethoxysilane.

[0060] Furthermore, the particle size distribution of the zirconium diboride powder is concentrated between 1 and 5 μm.

[0061] Furthermore, the mass ratio of xylene to butyl acetate in the diluent is 1-0.5:0.5.

[0062] According to the technical solution of the present invention, the high temperature resistant and anti-corrosion aluminized coating is composed of an aluminized layer and a shielding layer, wherein the aluminized layer is formed by drying the aluminized slurry, the shielding layer is formed by heating and curing the shielding coating, and the coating is finally formed by completing the aluminum diffusion process after heat treatment. By introducing an associative polyurethane thickener into the aluminized slurry, the stability of the slurry and the thixotropy of the coating process can be guaranteed while reducing the amount of binder. Silicon elements are introduced into the aluminized layer by adding hydroxyl-terminated polydimethylsiloxane and polysilazane copolymer-coated modified flaky aluminum powder, and the reaction activity of the aluminum diffusion process is regulated in coordination with metal oxides such as cerium oxide and zirconium oxide. The shielding layer film-forming resin uses fully hydrogenated polysilazane, which can withstand the process temperature of low-temperature aluminization. The introduced zirconium boride can be oxidized at this temperature to generate zirconium oxide and boron oxide. The boron oxide melts and further forms a molten film layer on the outer surface of the shielding layer through capillary action, and cooperates with the flaky filler inside the shielding layer to block oxygen, so that the aluminum diffusion process can be completed in an air atmosphere.

[0063] Example 1

[0064] A high temperature resistant and anti-corrosion aluminized coating, the coating is composed of an aluminized layer and a shielding layer. The aluminized layer is formed by drying and thermally removing the aluminized slurry, the shielding layer is formed by heating and curing the shielding coating, and the coating is finally formed by completing the aluminum diffusion process through heat treatment.

[0065] The aluminizing slurry is a single-component coating, which is composed of a mixture of a binder, an associative polyurethane thickener, spherical aluminum powder, modified flaky aluminum powder, metal oxide and a solvent. 100 g of the aluminizing slurry is configured according to the proportion.

[0066] Element Specification Mass / g Binder Industrial Grade 3 Associative polyurethane thickener Industrial Grade 2 Spherical aluminum powder Industrial Grade 50 Modified flake aluminum powder self made 3 Metal oxides Analytical grade 0.5 Solvents self made 41.5

[0067] The binder is polyvinyl alcohol with a number average molecular weight of 15000;

[0068] The associative polyurethane thickener is a commercially available product BYK RHEOBYK-H 7625VF;

[0069] The spherical aluminum powder is composed of spherical aluminum powders with particle sizes concentrated in the range of 5 to 10 μm and 25 to 40 μm, mixed in a mass ratio of 8:2.

[0070] The modified flaky aluminum powder is a flaky aluminum powder coated with a copolymer of terminal hydroxyl polydimethylsiloxane and terminal methyl polysilazane, wherein the number average molecular weight of the terminal hydroxyl polydimethylsiloxane is 2500, the number average molecular weight of the terminal methyl polysilazane is 1500, and the flake diameter of the flaky aluminum powder is concentrated between 15 and 25 μm.

[0071] The metal oxide is selected from zirconium oxide with a particle size distribution of 5 to 10 μm.

[0072] The solvent of the aluminizing slurry is deionized water.

[0073] The shielding coating is a single-component coating, which is composed of a mixture of a film-forming resin, a modified flaky filler, zirconium diboride powder, a functional additive and a diluent, and 100 g of the shielding coating is configured according to the proportion.

[0074] Element Specification Mass / g Film-forming resin Industrial Grade 50 Modified flake filler self made 15 Zirconium diboride Industrial Grade 8 Functional additives Industrial Grade 2 Thinner Industrial Grade 30

[0075] The film-forming resin is vinyl-terminated perhydropolysilazane with a number average molecular weight of 1500.

[0076] The modified flake filler is hexagonal boron nitride modified by trimethylmethoxysilane, and the hexagonal boron nitride flake layer diameter distribution is concentrated between 15 and 25 μm.

[0077] The particle size distribution of the zirconium diboride powder is concentrated between 1 and 5 μm.

[0078] The functional additive is composed of 1.5 g of a dispersing additive and 0.5 g of an anti-precipitation additive.

[0079] The diluent is prepared by mixing 15 g of xylene and 15 g of butyl acetate.

[0080] A method for preparing a high temperature resistant and anti-corrosion aluminized coating in air atmosphere, the method comprising the following steps:

[0081] (I) Preparation of aluminized layer

[0082] (1) Preparation of modified flaky aluminum powder: Dissolve terminal methyl polysilazane in xylene, the mass ratio of polysilazane to solvent is 1:20, recorded as solution A. Dissolve terminal hydroxyl polydimethylsiloxane in the same solvent, the mass ratio of terminal hydroxyl polydimethylsiloxane to solvent is 1:10, recorded as solution B. Disperse untreated flaky aluminum powder in solution A, the mass ratio of the two is 1:5. After the dispersion temperature stabilizes, weigh solution B and add it dropwise to solution A, the mass ratio of solution A to solution B is 1:0.5. After the addition is completed, stir the reaction in a 150°C oil bath under nitrogen atmosphere with condensation reflux for 2 to 3 hours, filter the product and wash it with acetone for several times, place it in a vacuum oven at 50 to 80°C and dry it for 6 to 8 hours, and finally obtain modified flaky aluminum powder.

[0083] (2) Preparation of aluminizing slurry: Weigh the binder, associative polyurethane thickener, spherical aluminum powder, modified flaky aluminum powder, metal oxide and solvent according to the mass ratio, and preferentially dissolve the binder in the solvent. After the solution is clarified, place the binder solution, associative polyurethane thickener, spherical aluminum powder, modified flaky aluminum powder and metal oxide in a high-speed disperser, and disperse them at a high speed of 1000 rpm for 4 hours in a constant temperature water area of ​​10-25°C to finally obtain aluminizing slurry.

[0084] (3) Preparation of aluminized layer: The aluminized slurry is applied to the metal substrate by air spraying, dipping or brushing. After the coating is completely dried, the aluminized slurry layer is obtained. The film thickness of the aluminized slurry layer after drying is controlled to be 35 μm. The metal substrate coated with the aluminized slurry layer is directly placed in a muffle furnace at 500° C. for 5 min of thermal debonding, and then cooled to room temperature in an air atmosphere to obtain an aluminized layer.

[0085] (II) Preparation of shielding layer

[0086] (1) Preparation of modified flake filler: Untreated hexagonal boron nitride is dispersed in a 70% ethanol-water solution, and the dispersion is adjusted to be weakly acidic using formic acid or acetic acid for standby use; trimethylmethoxysilane is added to the mixture at a mass ratio of 0.05:1 to hexagonal boron nitride, and the mixture is stirred and reacted in a water bath at 80° C. with condensation reflux for 3 h, the product is filtered and washed, and then placed in an oven at 90° C. for drying to obtain a modified flake filler;

[0087] (2) Preparation of shielding coating: Weigh the modified film-forming resin, modified anticorrosive filler, various additives and diluents according to the mass ratio, place them in a container to obtain a mixture, and grind it in a sand mill to control the overall particle size of the mixture to be less than 25 μm, to obtain a mixed shielding coating;

[0088] (3) Preparation of shielding layer

[0089] The shielding coating is applied on the surface of the aluminized layer by air spraying or brushing. After the coating is completely dry, the shielding layer is obtained. The total film thickness of the shielding layer and the aluminized layer is controlled to be 80 μm.

[0090] (III) Heat treatment of coating in air atmosphere

[0091] The metal substrate coated with the aluminized layer and the shielding layer is placed in a muffle furnace, and the temperature is increased to 500°C at a heating rate of 1-2°C / min. After keeping warm for 60 minutes, the temperature is increased to 700°C at a heating rate of 5-10°C / min. After keeping warm for 2 hours, the temperature is cooled to 150°C at a cooling rate of 10-15°C / min, and then taken out of the muffle furnace and cooled to room temperature in air. The metal substrate is the prepared high-temperature resistant and corrosion-resistant aluminized coating.

[0092] The high temperature resistant and anti-corrosion aluminized coating is prepared in an air atmosphere. The coating has excellent oxidation resistance and corrosion resistance. It can withstand thermal oxidation at 1000°C for 100 hours and neutral salt spray corrosion for 3000 hours. The coating does not bubble, crack or fall off.

[0093] Example 2

[0094] A high temperature resistant and anti-corrosion aluminized coating, the coating is composed of an aluminized layer and a shielding layer. The aluminized layer is formed by drying and thermally removing the aluminized slurry, the shielding layer is formed by heating and curing the shielding coating, and the coating is finally formed by completing the aluminum diffusion process through heat treatment.

[0095] The aluminizing slurry is a single-component coating, which is composed of a mixture of a binder, an associative polyurethane thickener, spherical aluminum powder, modified flaky aluminum powder, metal oxide and a solvent. 100 g of the aluminizing slurry is configured according to the proportion.

[0096] Element Specification Mass / g Binder Industrial Grade 4 Associative polyurethane thickener Industrial Grade 0.5 Spherical aluminum powder Industrial Grade 50 Modified flake aluminum powder self made 3 Metal oxides Analytical grade 0.5 Solvents self made 42

[0097] The binder is polyethylene glycol with a number average molecular weight of 10,000;

[0098] The associative polyurethane thickener is a commercially available product. Viscoplus 3030;

[0099] The spherical aluminum powder is composed of spherical aluminum powders with particle sizes concentrated in 5-10 μm and 25-40 μm in a mass ratio of 7:3.

[0100] The modified flaky aluminum powder is a flaky aluminum powder coated with a copolymer of terminal hydroxyl polydimethylsiloxane and terminal vinyl polysilazane, wherein the number average molecular weight of the terminal hydroxyl polydimethylsiloxane is 2500, the number average molecular weight of the terminal vinyl polysilazane is 1500, and the flake diameter of the flaky aluminum powder is concentrated between 15 and 25 μm.

[0101] The metal oxide is selected from zirconium oxide with a particle size distribution of 5 to 10 μm.

[0102] The solvent of the aluminizing slurry is deionized water.

[0103] The shielding coating is a single-component coating, which is composed of a mixture of a film-forming resin, a modified flaky filler, zirconium diboride powder, a functional additive and a diluent, and 100 g of the shielding coating is configured according to the proportion.

[0104] Element Specification Mass / g Film-forming resin Industrial Grade 45 Modified flake filler self made 15 Zirconium diboride Industrial Grade 5 Functional additives Industrial Grade 2 Thinner Industrial Grade 33

[0105] The film-forming resin is a methyl-terminated perhydropolysilazane having a number average molecular weight of 1500.

[0106] The modified flake filler is hexagonal boron nitride modified by vinyltriethoxysilane, and the hexagonal boron nitride flake layer diameter distribution is concentrated between 15 and 25 μm.

[0107] The particle size distribution of the zirconium diboride powder is concentrated between 1 and 5 μm.

[0108] The functional additive is composed of 1.5 g of a dispersing additive and 0.5 g of an anti-precipitation additive.

[0109] The diluent is xylene.

[0110] A method for preparing a high temperature resistant and anti-corrosion aluminized coating in air atmosphere, the method comprising the following steps:

[0111] (I) Preparation of aluminized layer

[0112] (1) Preparation of modified flaky aluminum powder: Dissolve terminal methyl polysilazane in xylene, the mass ratio of polysilazane to solvent is 1:15, recorded as solution A. Dissolve terminal hydroxyl polydimethylsiloxane in the same solvent, the mass ratio of terminal hydroxyl polydimethylsiloxane to solvent is 1:10, recorded as solution B. Disperse untreated flaky aluminum powder in solution A, the mass ratio of the two is 1:5. After the dispersion temperature stabilizes, weigh solution B and add it dropwise to solution A, the mass ratio of solution A to solution B is 1:0.3. After the dropwise addition is completed, stir the reaction in a 150℃ oil bath under nitrogen atmosphere with condensation reflux for 2 to 3 hours, filter the product and wash it with acetone for several times, place it in a vacuum oven at 50 to 80℃ and dry it for 6 to 8 hours, and finally obtain modified flaky aluminum powder.

[0113] (2) Preparation of aluminizing slurry: Weigh the binder, associative polyurethane thickener, spherical aluminum powder, modified flaky aluminum powder, metal oxide and solvent according to the mass ratio, and preferentially dissolve the binder in the solvent. After the solution is clarified, place the binder solution, associative polyurethane thickener, spherical aluminum powder, modified flaky aluminum powder and metal oxide in a high-speed disperser, and disperse them at a high speed of 800 rpm for 6 hours in a constant temperature water area of ​​10-25°C to finally obtain aluminizing slurry.

[0114] (3) Preparation of aluminized layer: The aluminized slurry is applied to the metal substrate by air spraying, dipping or brushing. After the coating is completely dried, the aluminized slurry layer is obtained. The film thickness of the aluminized slurry layer after drying is controlled to be 50 μm. The metal substrate coated with the aluminized slurry layer is directly placed in a muffle furnace at 500° C. for 5 min of thermal debonding, and then cooled to room temperature in an air atmosphere to obtain an aluminized layer.

[0115] (II) Preparation of shielding layer

[0116] (1) Preparation of modified flake filler: Untreated hexagonal boron nitride is dispersed in a 95% ethanol-water solution, and the dispersion is adjusted to be weakly acidic using formic acid or acetic acid for standby use; vinyl triethoxysilane is added to the mixture at a mass ratio of 0.03:1 to hexagonal boron nitride, and the mixture is stirred and reacted in a water bath at 80° C. with condensation reflux for 3 h, the product is filtered and washed, and then placed in an oven at 90° C. for drying to obtain a modified flake filler;

[0117] (2) Preparation of shielding coating: Weigh the modified film-forming resin, modified anticorrosive filler, various additives and diluents according to the mass ratio, place them in a container to obtain a mixture, and grind it in a sand mill to control the overall particle size of the mixture to be less than 25 μm, to obtain a mixed shielding coating;

[0118] (3) Preparation of shielding layer

[0119] The shielding coating is applied on the surface of the aluminized layer by air spraying or brushing. After the coating is completely dry, the shielding layer is obtained. The total film thickness of the shielding layer and the aluminized layer is controlled to be 80 μm.

[0120] (III) Heat treatment of coating in air atmosphere

[0121] The metal substrate coated with the aluminized layer and the shielding layer is placed in a muffle furnace, and the temperature is increased to 500°C at a heating rate of 1-2°C / min. After keeping warm for 60 minutes, the temperature is increased to 700°C at a heating rate of 5-10°C / min. After keeping warm for 2 hours, the temperature is cooled to 150°C at a cooling rate of 10-15°C / min, and then taken out of the muffle furnace and cooled to room temperature in air. The metal substrate is the prepared high-temperature resistant and corrosion-resistant aluminized coating.

[0122] The high temperature resistant and anti-corrosion aluminized coating is prepared in an air atmosphere. The coating has excellent oxidation resistance and corrosion resistance. It can withstand thermal oxidation at 1000°C for 100 hours and neutral salt spray corrosion for 3000 hours. The coating does not bubble, crack or fall off.

[0123] The above is only a specific embodiment of the present invention, and the present invention is described in detail. The unexplained part is a conventional technology. However, the protection scope of the present invention is not limited to this. Any changes or substitutions that can be easily thought of by any technician familiar with the technical field within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. The protection scope of the present invention shall be based on the protection scope of the claims.

Claims

1. A method for preparing a high temperature resistant and anti-corrosion aluminized coating, characterized in that: include: Step S1: Preparation of the infiltration layer: The aluminized slurry is applied on the metal substrate by air spraying, dipping or brushing. After the coating is completely dried, the aluminized slurry layer is obtained. The film thickness of the aluminized slurry layer after drying is controlled to be 30 to 50 μm. The metal substrate coated with the aluminized slurry layer is directly placed in 450 to 500° C. for 5 to 10 minutes of thermal debonding, and then cooled to room temperature in an air atmosphere to obtain the aluminized layer. Step S2: Preparation of shielding layer: Apply shielding coating on the surface of aluminized layer by air spraying or brushing, and obtain shielding layer after the coating is completely dry, and control the total film thickness of shielding layer and aluminized layer to be no more than 80 μm; Step S3: Heat treatment of the coating in air atmosphere: heat the metal substrate coated with the aluminized layer and the shielding layer to 500°C at a heating rate of 1-2°C / min, keep it warm for 30-60 minutes, then heat it to 700°C at a heating rate of 5-10°C / min, keep it warm for 1.5-2 hours, cool it to 150°C at a cooling rate of 10-15°C / min, and then cool it to room temperature in air. The metal substrate is then coated with the high temperature resistant and anti-corrosion aluminized coating.

2. The method according to claim 1, characterized in that Step S1 also includes the preparation of modified flaky aluminum powder: Take a solvent such as toluene, xylene or n-hexane to dissolve terminal methyl or terminal vinyl polysilazane, the mass ratio of polysilazane to solvent is 1:15-25, recorded as solution A, take the same solvent to dissolve terminal hydroxyl polydimethylsiloxane, the mass ratio of terminal hydroxyl polydimethylsiloxane to solvent is 1:5-10, recorded as solution B, disperse flaky aluminum powder in solution A, the mass ratio of the two is 1:5-10, after the dispersion temperature is stable, weigh solution B and add it dropwise into solution A, the mass ratio of solution A to solution B is 1:0.3-0.5, after the dropwise addition is completed, under nitrogen atmosphere and condensation reflux, stir the reaction in an oil bath at 120-150°C for 2-3h, filter the product and wash it with acetone for multiple times, place it in a vacuum at 50-80°C and dry it for 6-8h to obtain modified flaky aluminum powder.

3. The method according to claim 1, characterized in that Step S1 also includes the preparation of aluminizing slurry: weighing a binder, an associative polyurethane thickener, spherical aluminum powder, modified flaky aluminum powder, a metal oxide and a solvent according to a mass ratio, first dissolving the binder in the solvent, and after the solvent is clarified, dispersing the binder solution, the associative polyurethane thickener, the spherical aluminum powder, the modified flaky aluminum powder and the metal oxide at a high speed in a constant temperature water area of ​​10 to 25°C to finally obtain aluminizing slurry.

4. The method according to claim 1, characterized in that: Step S2 also includes the preparation of a modified anti-corrosion filler: dispersing hexagonal boron nitride in a 70% to 95% ethanol-water solution, adjusting the above dispersion to a weakly acidic state using formic acid or acetic acid; adding one of trimethylmethoxysilane and vinyltriethoxysilane in a mass ratio of 0.01 to 0.05:1 to hexagonal boron nitride to the mixture, stirring the reaction in a water bath at 40 to 80°C with condensation reflux for 1 to 3 hours, filtering and washing the product, and drying it at 80 to 90°C to obtain a modified anti-corrosion filler.

5. The method according to claim 4, characterized in that The method also includes the preparation of shielding coating: modified film-forming resin, modified anticorrosive filler, various additives and diluents are weighed according to the mass ratio, mixed and ground, and the particle size of the mixture is less than 25 μm to obtain shielding coating.

6. The method according to claim 3, characterized in that The spherical aluminum powder accounts for 35-50% of the mass of the aluminizing slurry.

7. The method according to claim 3, characterized in that The modified flaky aluminum powder accounts for 3-6% of the mass of the aluminizing slurry and is flaky aluminum powder coated with a copolymer of terminal hydroxyl polydimethylsiloxane and polysilazane.

8. The method according to claim 3, characterized in that The metal oxide accounts for 0.5-1% of the mass of the aluminizing slurry and is one of cerium oxide and zirconium oxide.

9. The method according to claim 3, characterized in that: The spherical aluminum powder is composed of a compound of spherical aluminum powders with particle sizes concentrated in 5-10 μm and 25-40 μm, and the mass ratio of the two is 6-8:2-4.

10. A high temperature resistant and anti-corrosion aluminized coating, characterized in that: The coating is prepared by any of the methods described in claims 1-9, and includes an aluminized layer and a shielding layer, wherein the aluminized layer is formed by drying and thermally debonding the aluminized slurry, and the shielding layer is formed by heating and curing the shielding coating, and the coating is finally formed by completing the aluminum diffusion process through heat treatment.

Citation Information

Patent Citations

  • Novel cast iron surface aluminized coating preparation method

    CN109023210A

  • Low-density anticorrosive paint and preparation method thereof

    CN116396669A

  • High-temperature-oxidation-resistant protective coating for titanium alloy surface and preparation method of high-temperature-oxidation-resistant protective coating

    CN116445018A

  • Method for preparing aqueous non-stick coating modified with carbon nanotube composite ceramic network

    WO2021128879A1

  • Heat-conducting wave-absorbing auxiliary agent, low-temperature curing coating, heavy corrosion-resistant coating, and preparation method therefor and use thereof

    WO2024149031A1